ChemInform Abstract: N‐Heterocyclic Carbene Ligands Bearing Poly(ethylene Glycol) Chains: Effect of the Chain Length on Palladium‐Catalyzed Coupling Reactions Employing Aryl Chlorides. Issue 15 (24th March 2016) - Fujihara, Tetsuaki; Yoshikawa, Takahiro; Satou, Motoi; Ohta, Hidetoshi; Terao, Jun; Tsuji, Yasushi
Abstract: The catalyst with a poly(ethylene glycol) chain length of averagely 17 ethylene glycol units is found to be highly active for the Suzuki reaction.